Nutritional Status and Cognitive Development in Children Aged 2-5: A Narrative Review - Ismail, Fauziah; Fasrini, Ulya Uti; Harmen, Anggia Perdana (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2025)
Background: Meeting the nutritional needs of children is crucial for optimal growth and development. Children aged 2-5 years are in the preoperational stage, characterized by egocentric and intuitive thinking. Nutritional deficiencies can negatively impact their development, including cognitive abilities and learning capacity. Research worldwide has extensively studied the relationship between nutritional status and children's development, emphasizing the importance of proper nutrition for motor, speech, and behavioral skills essential for learning. This narrative review presents the results of relevant research from various countries on the relationship between nutritional status and the development of children aged 2-5 years in terms of motor skills, speech, and behavior. Methods: This review is a narrative review of relevant articles from the last decade, focusing on the discussion of the cognitive development process of children and its relationship to nutritional status. Results: Several studies have linked nutritional status with overall development, while some have specifically focused on motor or cognitive development. Although most results indicate a relationship between nutritional status and the development of children aged 2-5 years, the observed developmental levels and achievements are not entirely conclusive. Child development is also influenced by external factors. Conclusion: A total of 11 articles from 18 articles stated that there was a significant relationship between nutritional status and children’s cognitive development.